Impact evaluation of imperfect channel state information on the performance of downlink CoMP systems - Batista, Rodrigo Lopes (2011)
Coordinated Multi-Point (CoMP) systems promise very high performance in terms of spectral efficiency and coverage benefits when perfect Channel State Information (CSI) is available at the transmitter. However, perfect CSI is difficult to obtain in CoMP systems due to an increased number of channel parameters to estimate at the receiver and to be fed back to the transmitter. So, the performance of such systems is compromised when the CSI is not perfectly known during CoMP processing such that it is an important problem to be addressed. This paper provides system-level analyses for strategies of Radio Resource Allocation (RRA) in CoMP systems, which consider dynamic Space Division Multiple Access (SDMA) grouping and joint precoding and power allocation for Signal to Interference- plus-Noise Ratio (SINR) balancing, and assumes imperfect CSI in order to achieve more accuracy with regard to the real- world implementations. Our results show a critical degradation on performance of the CoMP systems due to imperfect CSI.